Searching for effective strategies to reach boys and young men; a mixed-methods study protocol for youth clinics in Sweden - Mazen Baroudi (BMC Health Services Research)
Abstract Background Efforts to engage boys and young men in sexual and reproductive health (SRH) services in Sweden remain limited, with only a small proportion accessing youth clinics, the primary providers of such services. Existing initiatives are often ad-hoc and lack institutionalization within public policy and practice. This study aims to identify feasible and effective interventions to improve boys’ and young men’s access to youth clinics in Sweden. Methods Employing a mixed-methods approach, this study investigates interventions, strategies, and factors influencing access to SRH services for boys and young men in Sweden. Firstly, a systematic literature review will be conducted to identify evaluated interventions globally. Secondly, strategies to attracts boys and young men in youth clinics in Sweden will be mapped. Thirdly, case studies in two regions in Sweden – chosen for their demographic and geographic diversity – will be conducted interviewing healthcare providers, managers, policymakers, and boys and young men. Lastly, Q-methodology will be used to rank all identified strategies. Healthcare providers and managers will rank these strategies based on their perceived effectiveness and feasibility while boys and young men will rank the interventions based on perceived effectiveness. Discussion The added value of this project is generating robust evidence regarding boys and young men’s involvement in SRH services, especially their access to youth clinics. This is crucial for (1) developing gender-sensitive services and service delivery models that effectively promote young men’s SRH; (2) informing future young men’s health policies ensuring that their unique SRH concerns are addressed; and (3) improving young men’s participation in SRH provision. This will ultimately foster a culture of shared responsibilities and advance gender equality.